Co-encapsulation of curcumin and salicylic acid in mucoadhesive polymer nanoparticles - Cristian Moreno, Jorge Forero, Yolima Baena, Leon Perez (Journal of Applied Pharmaceutical Science, 2024)
Colorectal cancer poses a significant global health challenge with high incidence and mortality rates, as reported by the World Health Organization. Natural compounds such as curcumin (Cur) and salicylic acid (SCA) have shown promising therapeutic effects against colorectal cancer. However, their oral administration is hindered by their low bioavailability. This study aimed to develop mucoadhesive nanoparticles capable of co-encapsulating Cur and SCA using a double-emulsion process. The copolymer m-PEG-b-PCL, which is considered a safe material for biomedical applications, was chosen as the polymeric precursor, while chitosan, which has mucoadhesive properties, served as the emulsion stabilizer. Through the optimization of drug concentrations, polymer molecular weights, and stabilizer type and concentration, a formulation composed of spherical nanoparticles with an average hydrodynamic diameter of 355 nm and an entrapment efficiency of 13.70% for Cur and 90.72% for SCA was obtained. The release kinetics showed sustained release over 24 hours. Moreover, these nanoparticles demonstrated strong adhesion to the colonic mucosa, presenting a potential localized drug delivery strategy. Co-encapsulation of Cur and SCA within mucoadhesive polymer nanoparticles holds great potential for significantly enhancing the therapeutic outcomes of colorectal cancer treatment.
Keywords: Polymer nanoparticles, curcumin, salicylic acid, co-encapsulation